2011
DOI: 10.3102/0002831210387916
|View full text |Cite
|
Sign up to set email alerts
|

A Validity Argument Approach to Evaluating Teacher Value-Added Scores

Abstract: Value-added models have become popular in research and pay-forperformance plans. While scholars have focused attention on some aspects of their validity (e.g., scoring procedures), others have received less scrutiny. This article focuses on the extent to which value-added scores correspond to other indicators of teacher and teaching quality. The authors compared 24 middle school mathematics teachers' value-added scores, derived from a large (N = 222) district data set, to survey-and observation-based indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(203 citation statements)
references
References 40 publications
(79 reference statements)
6
189
0
4
Order By: Relevance
“…Using samples that varied in size from just 24 teachers (Grossman et al, 2013;Hill et al, 2011) to over 3,000 teachers in seven districts across the country (the Measures of Effective Teaching [MET] project) (Kane & Staiger, 2012;Mihaly et al, 2013), these studies tested multiple observational instruments and relied on expert reviewers to observe live and videotaped lessons. Simple and disattenuated correlations between the scores from the instructional standards of observation-based measures and "underlying" value-added measures of teacher effectiveness ranged in the MET study from 0.11 to 0.28 in reading or English Language Arts (ELA) and from 0.18 to 0.41 in math (Kane & Staiger, 2012;Mihaly et al, 2013).…”
Section: Summary Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Using samples that varied in size from just 24 teachers (Grossman et al, 2013;Hill et al, 2011) to over 3,000 teachers in seven districts across the country (the Measures of Effective Teaching [MET] project) (Kane & Staiger, 2012;Mihaly et al, 2013), these studies tested multiple observational instruments and relied on expert reviewers to observe live and videotaped lessons. Simple and disattenuated correlations between the scores from the instructional standards of observation-based measures and "underlying" value-added measures of teacher effectiveness ranged in the MET study from 0.11 to 0.28 in reading or English Language Arts (ELA) and from 0.18 to 0.41 in math (Kane & Staiger, 2012;Mihaly et al, 2013).…”
Section: Summary Of Related Literaturementioning
confidence: 99%
“…We consider these studies in two groups: those that analyze the relationships between observation-based measures and VAMs in a purely research context (e.g., Grossman, Loeb, Cohen, & Wyckoff, 2013;Hill, Kapitula, & Umland, 2011;Kane & Staiger, 2012;and Mihaly, McCaffrey, Staiger, & Lockwood, 2013) and those that assess these relationships as measured in the implementation of systems in practice (e.g., Kane, Taylor, Tyler, & Wooten, 2011;Sartain et al, 2011;TDOE, 2012). These studies vary in their implementation context (research versus practice), as well as in the observational measures employed (those that examine just the classroom-based aspects of observational measures and those that explore the whole measure) and in the methods used to estimate relationships between observational and test-based measures of teacher effectiveness.…”
Section: Summary Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that higher MKT is positively correlated with a teacher's ability to select and enact mathematically rich tasks in elementary school classrooms (Charalambous, 2010), higher quality of instructional practices (Hill, Kapitula, and Umland, 2011), and student achievement in mathematics (Hill, Rowan, and Ball, 2005).…”
Section: Teacher Content Knowledgementioning
confidence: 99%
“…Gates, 2012;Wiggins, 2012;Winters, 2012). Skeptics of VAMs argue that we should be cautious in adopting the models, particularly if the aim is to use them to make comparisons between teachers or for individual personnel decisions because their reliability and validty are suspect (e.g., Au, 2007;Corcoran, 2010;Darling-Hammond, Amrein-Beardsely, Haertel, & Rothstein, 2012;Hill, Kapitula, & Umland, 2010). There is concern about how VAMs rely on standardized tests, which may not be up to the task of individual teacher evaluation (Amrein-Beardsley, 2009;Papay, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%